Background music cultures in Finnish urban life - Uimonen, Heikki; Kilpiö, Kaarina; Kytö, Meri (Cambridge elements. Elements in music and the city, 2024)
This Element focuses on how music is experienced, articulated, and reclaimed in urban commercial environments. Special attention is paid to listeners, spaces, and music, co- and re-produced continuously in their triangular relationship affected by social, legal, economic, and technological factors. The study of the historical development of background music industries, construction of contemporary sonic environments, and individual meaning-making is based on extensive data gathered through interviews, surveys, and fieldwork, and supported by archival research. Due to the Finnish context and the ethnomusicological approach, this study is culture-sensitive, providing a fresh 'factory-to-consumer' perspective on a phenomenon generally understood as industry-lead, behavioral, and global. This title is also available as Open Access on Cambridge Core.